A Brain Region-Specific Expression Profile for Genes Within Large Introgression Deserts and Under Positive Selection in Homo sapiens - Buisan, Raül; Moriano, Juan; Andirkó, Alejandro; Boeckx, Cedric (Frontiers in Cell and Developmental Biology, 2022)
Analyses of ancient DNA from extinct hominins have provided unique insights into the complex evolutionary history of Homo sapiens, intricately related to that of the Neanderthals and the Denisovans as revealed by several instances of admixture events. These analyses have also allowed the identification of introgression deserts: genomic regions in our species that are depleted of 'archaic' haplotypes. The presence of genes like FOXP2 in these deserts has been taken to be suggestive of brain-related functional differences between Homo species. Here, we seek a deeper characterization of these regions and the specific expression trajectories of genes within them, taking into account signals of positive selection in our lineage. Analyzing publicly available transcriptomic data from the human brain at different developmental stages, we found that structures outside the cerebral neocortex, in particular the cerebellum, the striatum and the mediodorsal nucleus of the thalamus show the most divergent transcriptomic profiles when considering genes within large introgression deserts and under positive selection.